LEGAL PROTECTION FOR THE PUBLIC AGAINST LOCAL GOVERNMENT ADMINISTRATIVE DECISIONS IN WEST JAVA - Taty Sugiarti (PT. Radja Intercontinental Publishing, 2023)
Administrative decisions issued by local governments directly affect citizens’ legal positions in licensing, personnel affairs, public services, social assistance, land administration, and other governmental matters. This article analyzes the construction of legal protection against detrimental local-government administrative decisions and examines its application in West Java through Bandung State Administrative Court Decision Number 123/G/2019/PTUN-BDG. The study employs normative legal research using statutory, conceptual, and case approaches. Primary legal materials consist of legislation on administrative courts, government administration, local government, public services, Supreme Court Regulation Number 6 of 2018, and the relevant court decision; secondary materials comprise recent administrative-law scholarship. The study finds that effective protection must operate in layers. Preventive protection requires lawful authority, proper procedure, adequate reasons, accurate factual verification, transparency, and compliance with the General Principles of Good Governance. Repressive protection is provided through administrative objections and appeals, judicial review before the State Administrative Court, and effective compliance with final judgments. The Bandung case demonstrates that judicial protection may correct a defect of authority even when the substantive basis of a personnel decision remains legally supportable. Therefore, legal protection should not be understood merely as a mechanism to reverse governmental outcomes, but as an institutional guarantee that every adverse decision is produced by a competent authority through a lawful and accountable process. For local governments in West Java, stronger ex ante legal review, accessible administrative remedies, standardized notice of remedies, and systematic monitoring of judgment compliance are recommended.